Optimal Under - frequency Load Shedding using Cuckoo Search with Levy Flight Algorithm for Frequency Stability Improvement - Mwaniki, C; Muriithi, C M.; Abungu, N.O; Nyakoe, G N. (International Journal of Emerging Technology and Advanced Engineering, 2015)
Frequency stability in a power system is very important as it determines the synchronous speed of electrical machines. Therefore it should remain within acceptable limits even when the system is disturbed. In order to ensure that frequency stability is achieved, load shedding is a countermeasure taken as a last resort. However, its consequences might result in huge technical and economic losses. Therefore, this control measure should be optimally and carefully carried out. This paper proposes Cuckoo search with Levy flights (CSwLF) based algorithm for solving the optimal load shedding problem. The amount of load shedding at each bus is determined by applying CSwLF to solve a nonlinear optimization problem formulated in the optimal power flow framework. The performance of the proposed CSwLF based method is tested on the operating conditions of IEEE 14-bus test system. The results shows that load shedding can be done discriminately in a single step to bring back a system from danger of frequency instability
Keywords: Metaheuristic algori thm; Frequency stability; under voltage load shedding; cuckoo searc; Levy flights